Movement in the streets: Significant spatial features of the historic center of Quito - Piñeiros, Estefanía (2023)
The urban imaginary of the historical centre of Quito is strongly linked to the configuration of the Ecuadorian national identity and to the official patrimonial discourse which guide the planning and management of the city centre while ignoring the daily spatial relationships and local memories that make up a different city. Therefore, this research seeks to understand how the residents, merchants and artisans of the city centre experience, think and value their space. This research uses a mobile ethnography and combines different qualitative tools such as mapping and photography to analyse corporeal and affective experiences in the city. The inhabitants use the notion of movement to describe an abundant flow of people, money and goods in different places and streets. The research identifies a variety of places in and around the historic centre remembered by the inhabitants for their movement and related to positive emotions and a sense of place. The article identifies and discusses how the relationship between movement, transportation and popular commerce generates affective atmospheres and problematizes the loss of movement of different public spaces that are currently perceived by the inhabitants as empty and dead. The article proposes that the places of movement evoke another type of popular imaginary and generate an alternative urban identity.